The ethical challenges of brain-computer interfaces in healthcare - Masitise, Mots’abi Elizabeth (Stellenbosch : Stellenbosch University, 2025)
Masitise, Mots’abi Elizabeth. 2025. The ethical challenges of brain-computer interfaces in healthcare. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/132634